Human values for managers - Chakraborty, S. K. (New Delhi, India: A. H. Wheeler & Co Ltd., 1995)
The book reflects on the concepts, principles and practices of psychology and philosophy in the Indian sub-continent.
occ 17/01/2019
Loans
Keywords: Management; Business ethics; Executives--Attitudes; Executives--Conduct of life; India